Development of Smart Apps Creator-Based Learning Media on Religious Diversity Materials in Indonesia - Galih Puji Mulyoto; Luthfia Aldila Arsy Subagyo Subagyo; Sutomo (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to develop a product that is tested to be valid and interest so that it is can help the student learning process in understanding the material on religious diversity in Indonesia. The research method used is Research and Development (R&D) by applying the ADDIE development model. The results of this study are in the form of learning media products based on smart apps creators that very valid criteria (86%) from material expert validators and media with valid criteria from media expert validators (80%) and media is also categorized as a very interesting (82.7%). Based on the validation results and the results of field trials, it can be concluded that the smart apps creator-based learning media that contains material on religious diversity is very valid and very interesting to be used as a Civics learning medium in class IV MI Perwanida Blitar.